“BEING UNITED WE CLOSE, BEING APART WE DIE”: COMMON COMBAT AGAINST COVID-19 IN DENSEST VILLAGE - Nofrida Panjaitan; Joko Adianto (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
The spread of pneumonia cases caused by a new type of Coronavirus (Novel Coronavirus) SARS Cov-2 was established by WHO called Coronavirus Disease 2019 (COVID-19) on February 2020 and designated as a pandemic on March 11, 2020. However, an interesting phenomenon arises, despite the high number of COVID-19 spread in Jakarta. That is as of April 10, 2020, 50 out of 267 urban villages in Jakarta are declared free of COVID-19 (not infected with the virus) and one of them is the most populous village in Jakarta called the most densely populated urban village in Southeast Asia, namely Kalianyar in Tambora Sub District, West Jakarta.This study aims to find out how does Kalianyar combat the spread of COVID-19, recalling that considering the nature of the virus transmission, Kalianyar has high potential to be a vulnerable zone. The research was conducted through a qualitative analysis on a case study of Kalianyar aiming to examine the deep explanation and understanding of distinctive implementation and to obtain the lesson learned from the implementation of Fournier's idea seeing how the common process occurs. The common process occurring within social organization in Kalianyar shows that there are relational and reciprocal relationships resulting from each activity related to the three axes as suggested by Fournier.